Drivers of the summer 2024 marine heatwave and record salmon lice outbreak in northern Norway - Silvana Gonzalez; Anne D. Sandvik; Mari F. Jensen; Jon Albretsen; Anne Britt Sandø; Randi B. Ingvaldsen; Solfrid S. Hjøllo; Frode Vikebø (Communications Earth & Environment)
Abstract Marine heatwaves are prolonged periods of extreme ocean warming that can strongly impact marine ecosystems, fisheries, and aquaculture. In August 2024, northern Norway experienced one of its most intense marine heatwaves on record, with sea surface temperatures exceeding 18 °C—more than 4 °C above the long-term average. This event contributed to an unprecedented salmon lice outbreak at aquaculture sites, causing increased fish mortality and economic losses. Here we use numerical ocean model hindcast data, atmospheric reanalysis data, and in situ observations to identify the factors behind this event. Local weather conditions, including high solar radiation, unusually warm air temperatures, and weak winds, caused increased heat transfer to the sea surface and reduced ocean mixing. Additionally, large-scale atmospheric pressure patterns intensified warm air advection and freshwater transport along the coast, reinforcing local stratification and warming. These findings highlight the importance of advancing regional marine heatwave forecasting to support fisheries and aquaculture resilience under a warming climate.